Current Perspectives on Coronavirus Disease 2019 and Cardiovascular Disease: A White Paper by the JAHA Editors. Issue 12 (16th June 2020) - Gupta, Ajay K.; Jneid, Hani; Addison, Daniel; Ardehali, Hossein; Boehme, Amelia K.; Borgaonkar, Sanket; Boulestreau, Romain; Clerkin, Kevin; Delarche, Nicolas; DeVon, Holli A.; Grumbach, Isabella M.; Gutierrez, Jose; et al.
Abstract: Coronavirus Disease 2019 (COVID‐19) has infected more than 3.0 million people worldwide and killed more than 200, 000 as of April 27, 2020. In this White Paper, we address the cardiovascular co‐morbidities of COVID‐19 infection; the diagnosis and treatment of standard cardiovascular conditions during the pandemic; and the diagnosis and treatment of the cardiovascular consequences of COVID‐19 infection. In addition, we will also address various issues related to the safety of healthcare workers and the ethical issues related to patient care in this pandemic.